Um estudo sobre as expectativas acadêmicas e profissionais dos alunos ingressantes e concluintes da graduação em Ciências Contábeis nas universidades privadas da cidade de São Paulo - Silva, Mauricio Narciso da (2016)
Creating expectations is a necessary factor to achieve personal or professional success and therefore the research performs a diagnosis that will identify academic and professional expectations of the new students in relation to those who will probably graduate in 2016, but also analyze the reasons that lead students to join the program, identify their socioeconomic profiles, demonstrate the major difficulties that students encounter during the program and finally show what specific and basic subjects are considered most relevant to their training that impacts, somehow, in their professional expectation. Therefore, the research seeks to identify how to transform academic and professional expectations of entrants in relation to the graduates on the academic and professional development during the program. In various stages of the life, humans experience difficulties, since the career choice to the learning process, which requires greater attention of the student to avoid conflicts and lack of enthusiasm to stay and complete the training in higher education and consequently professional achievement. The methodology used in this research is descriptive and analyzes the collected primary data through two questionnaires given to the new students in 2016 and also to those who likely started the program in 2013 and are expected to complete the program in 2016. In addition to the primary data collected, the research takes secondary data obtained by the "Student Questionnaire" of ENADE 2012, which provides the profile of the student who probably joined the program in 2009. The data collected by the research allowed the identification of the socioeconomic profile of the students who entered the Accountancy Program in 2009, 2013 and 2016. In addition to the time analysis, the research also identified that more than 50% of the students who entered the Accountancy Program had identification with mathematical reasoning being this their motivation to choose the program. To conclude, the research shows that the academic and professional expectations of the students who will get the degree in 2016 are similar to the expectations of these same students when enrolled in the Accountancy Program